Concrete filled double steel tube columns incorporating UPVC pipes under uniaxial compressive load at ambient and elevated temperature. (June 2022) - Chang, Qiuying; Zhao, Chuanhai; Xing, Lei; Ahmad, Waqas; Javed, Muhammad Faisal; Aslam, Fahid; Musarat, Muhammad Ali; Vatin, Nikolai Ivanovich
Abstract: This experimental investigation reveals the projected benefits of concrete-filled double-skin tubular columns. These columns are made up of an outside steel tube, an interior UPVC pipe, and a sandwich of concrete among these tubes. The effect of the dimension ratio of the outer-to-inner tube, the thickness ratio of the outer tube, and the internal tube material (steel/UPVC) on the ultimate compressive strength of double-skin tubular columns samples filled with concrete are investigated. Finally, the experimental findings were compared to previously published design approaches in AISC (2010), GB50936 (2014), and EC4 (2004). The analysis revealed that GB50936 (2014) produces the best outcomes, followed by AISC (2010) and EC4 (2004). In addition, the samples were tested in elevated temperatures to study their post-fire axial capacity. It was discovered that the type of infilled concrete and interior tube material has no major impact on the performance of samples at elevated temperatures.